Paradoks Hubungan Petani Padi dan Tengkulak di Desa Sepanjang Kecamatan Glenmore Kabupaten Banyuwangi - Bryan Marshal Aflah; Elly Suhartini; Jati Arifiyanti (Prodi Sosiologi FISIP ULM, 2023)
Rice farming in the Sepanjang village's main income, but not all farmers have direct access to marketers such as factories, especially peasant who have limited land who ultimately choose to sell crops to middlemen using a patron-client system. The aim of this research is to find out, describe and analyze the paradoxical relationship between peasant and middlemen. The research was carried out in villages along Glenmore District, Banyuwangi Regency. The research method used is qualitative with a phenomenological approach. The research was carried out in April - June 2023. In the process of selling to middlemen, peasant get positive benefits such as getting loans, transportation accommodation and guaranteed marketing networks. However, in their relationship with middlemen, peasant also experience several negative things, such as fraud committed by middlemen, such as rounding off weigh figures, rounding off purchase prices and manipulation during the gabug or tare testing process. In this position, the peasant position becomes a paradox, namely that it lies in the condition where the peasant gets positive and negative sides in the relationship with middlemen simultaneously. In the theoretical realm, this research can be a reference point in developing research on the existence and relationships of patron-clients. In the practical realm, this research can be a point of consideration or considerations for determining regional and government policies, especially in the agricultural sector.